Case Report: Allergic Contact Dermatitis on a Carbon Black-Based Permanent Tattoo - Dana Parama Julius; Putu Dyah Ayu Saraswati; Edward Edwin; Ariel Ekaputra (PROMOTOR, 2026)
Allergic contact dermatitis (ACD) is a common dermatological complication caused by exposure to allergens, which can occur in tattooing. This case reports a 30-year-old man who experienced dermatitis lesions 1 day after a black permanent tattoo on his left arm. Symptoms appeared as pain, erythema, edema, and pustules in the tattoo area. Diagnosis was established based on clinical symptoms, tattoo procedure history, and response to therapy. Treatment with topical and systemic corticosteroids as well as antihistamines provided significant improvement in a short time, healing lesions, reducing symptoms and inflammation. However, similar cases may require more invasive procedures such as debridement and excision, especially if severe reactions occur. This case presents that black carbon ink, although often considered safe, can cause significant allergic reactions. Allergic and other skin reactions can be caused by the ink, additives, tools, and contamination such as metals. Understanding the ink composition, product regulations, and patient’s history is very important for the prevention of ACD. Case reporting and ongoing research are essential to expand tattoo safety data, clinical understanding, prevention, and management of tattoo-induced ACD.